Literature Review: A Study on Efficiency Enhancements, Comparative Analysis of TiO2 and ZnO-Based Dye-Sensitized Solar Cells - Suyadi, M. Ilham Andri; Saputra, Yureski Belly; Rusdianasari (International Journal of Research in Vocational Studies (IJRVOCAS), 2025)
Dye-Sensitized Solar Cells (DSSCs) have garnered significant attention due to their cost-effectiveness and potential for sustainable energy applications. TiO2 and ZnO nanostructures are widely employed as photoanodes, given their unique optical and electronic properties. This paper compares the findings of ten studies with similar research scopes, highlighting enhancements in DSSC efficiency using modified TiO2 and ZnO. Results are presented through comparative analysis and graphical representations, focusing on energy conversion efficiency. Through a detailed comparative analysis, this research identifies key trends and material innovations for advancing DSSC technology. Currently from these studies TiO2 with synthesis dye still hold the highest efficiency compared to ZnO and Synthesis TiO2/ZnO nanocomposite whether using synthesis and natural dye and by using counter electrode of Mg and Fe in TiO2 based have the least efficiency. DSSCs efficiency still lower than silicon based and thin-film solar cells but have the potential to be the cheapest solar cells. DSSCs need to improve efficiency to be able to go to marketplace and it needs further research and combination of dye and counter electrode or even the new breakthrough.